From the producer to the consumer: marketing strategies in contexts of uncertainty (Revista Ciencia Agraria, 2023)
Objective: To examine and evaluate the marketing strategies implemented in the Municipal Market of the city of Santa Rosa, located in the province of La Pampa, Argentina. Methodology: A case study with an observational, cross-sectional, and descriptive approach. The study is divided into two main perspectives: Firstly, 18 testimonials from municipal officials, producers, and consumers were collected. Secondly, current prices of 44 products grouped into four categories were compared, taking into account quality characteristics, in relation to the average of 10 retail markets, including greengrocers, supermarkets, and neighborhood stores. Results: It was identified that the different stakeholders involved in this market positively value attributes such as price, quality, and food variety. Additionally, price increases ranging from 5% to 83% were observed in local stores compared to the prices traded in the mentioned municipal market. Conclusion: The analyzed strategies are positively appreciated by both producers and consumers.
Keywords: commercialization; family economy; food; strategies